2018
DOI: 10.3390/w10030321
|View full text |Cite
|
Sign up to set email alerts
|

Household Water Demand in Andorra: Impact of Individual Metering and Seasonality

Abstract: Abstract:Despite the large literature focused on residential water use, our knowledge of the impact of individual metering on household water consumption remains limited. Our work aims to fill this gap by providing the first estimate of the residential water demand function in the Principality of Andorra, where collective and individual metering coexists. Using a panel dataset covering the years 2006 to 2015, we propose estimating a domestic water demand function for the municipality of Andorra La Vella (the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…These papers cover a large number of countries (Spain, France, Jordan, Australia, Bangladesh, Brazil, Lithuania, Peru, Poland, Russia, Serbia, Tanzania, Zambia, Zimbabwe, Colombia, India and Unites States of America). Some papers deal with the impact of water metering on residential water use (i.e., [46][47][48]), while others consider pricing policies (i.e., [49,50]), non-price policies (i.e., [51,52]) or the performance of water services (i.e., [53,54]). All selected papers contribute to a better understanding of residential water use, and they provide relevant results for policy-makers in charge of water management.…”
Section: Discussionmentioning
confidence: 99%
“…These papers cover a large number of countries (Spain, France, Jordan, Australia, Bangladesh, Brazil, Lithuania, Peru, Poland, Russia, Serbia, Tanzania, Zambia, Zimbabwe, Colombia, India and Unites States of America). Some papers deal with the impact of water metering on residential water use (i.e., [46][47][48]), while others consider pricing policies (i.e., [49,50]), non-price policies (i.e., [51,52]) or the performance of water services (i.e., [53,54]). All selected papers contribute to a better understanding of residential water use, and they provide relevant results for policy-makers in charge of water management.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented by Bergel et al (2016a) show some disproportions between the quarterly water consumption in the households noted in a four-year period, but these were especially related to the water consumption for additional purposes. Finally, Reynaud et al (2018) observed a strong quarterly seasonality of the water consumption in the case of single-family water users, in contrast to the multi-family water users.…”
Section: Introductionmentioning
confidence: 88%
“…Seasonal water supply for domestic consumption is a significant concern that affects water demand in households [1]. Ensuring a sustainable water supply to the world's population between now and 2030 is a major challenge because of the current depletion of water resources and increasing global population size.…”
Section: Introductionmentioning
confidence: 99%